If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -10 = -6 Reorder the terms: -10 + 4x = -6 Solving -10 + 4x = -6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + 4x = -6 + 10 Combine like terms: -10 + 10 = 0 0 + 4x = -6 + 10 4x = -6 + 10 Combine like terms: -6 + 10 = 4 4x = 4 Divide each side by '4'. x = 1 Simplifying x = 1
| (U+5)(u-3)= | | x-1/2x+14-x+5/9x+63 | | Ln(200)=ln(27x)+0.2x | | m+22=21 | | (2w^3-9w^5+2)10w^4= | | 2x+1=3y | | 8x^4(2-5x^2)= | | 180=12*x | | 6w^3(9w^7+4w)= | | 13=2*3.14*x | | (7/6n)+(1/2n)=5 | | 10.99=2*3.14*x | | 3x+6y=-2 | | 37.7=2*3.14*x | | 9x/2=49.5 | | x^2+x+5=65 | | 14x=49.5 | | (2w^2-7w^4+7)3w^5= | | 7x/2=49.5 | | 9w^2-9=0 | | 6y^2(10-9y^3)= | | 9(2x+5)=6(x-2)-3 | | 15*1.20= | | x^4+b*x^2+c=0 | | 2.40(1.20*15)= | | 5*x^3-x^2=0 | | 9(t-5)+5t=7(2t+5)-9 | | (x-3)(x+3)+(x-3)(x+8)= | | x+2y+5=0 | | 8a-6b=12 | | 3x^2-10x=-13x | | (-2)(-3)(5)(4)= |